2013
DOI: 10.1002/jcph.235
|View full text |Cite
|
Sign up to set email alerts
|

Abuse potential, pharmacokinetics, pharmacodynamics, and safety of intranasally administered crushed oxycodone HCl abuse‐deterrent controlled‐release tablets in recreational opioid users

Abstract: The objective of this study was to evaluate abuse potential, pharmacokinetics, pharmacodynamics, and safety of intranasally administered, crushed reformulated OxyContin® (oxycodone HCl controlled-release) tablets (ORF), relative to crushed original OxyContin® (OC), oxycodone powder (Oxy API), and OC placebo. This randomized, double-blind, positive- and placebo-controlled crossover study enrolled healthy, adult, nonphysically dependent recreational opioid users with recent history of intranasal drug abuse (N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 27 publications
(44 reference statements)
0
63
0
Order By: Relevance
“…In a clinical laboratory study of nondependent opioid users, 20 mg (0.29 mg/kg) oxycodone administered intravenously (Backonja et al, 2016) or 30 mg (0.43 mg/kg) administered as intranasal powder (Harris et al, 2014) produced significant drug-liking effects. These doses are at the lower end of the range administered to rats intravenously in the current study.…”
Section: Efficacy Of Vaccines For Opioid Use Disordersmentioning
confidence: 99%
“…In a clinical laboratory study of nondependent opioid users, 20 mg (0.29 mg/kg) oxycodone administered intravenously (Backonja et al, 2016) or 30 mg (0.43 mg/kg) administered as intranasal powder (Harris et al, 2014) produced significant drug-liking effects. These doses are at the lower end of the range administered to rats intravenously in the current study.…”
Section: Efficacy Of Vaccines For Opioid Use Disordersmentioning
confidence: 99%
“…Studies have shown that it is less attractive to recreational drug abusers than the original extended-release formulation. [101,102] Targiniq™ ER (Purdue Pharma LP) was approved in the USA in July 2014. This abuse-deterrent formulation contains oxycodone combined with naloxone -an antagonist that blocks the euphoric effects of oxycodone if the tablet is crushed for snorting or manipulated for injection.…”
Section: Differences In Routes Of Abuse Between Populationsmentioning
confidence: 99%
“…Tampering of codeine is no exception [46–48]. Still published research findings of assessments of harm, medicine misuse, and tampering will in some cases provide an additional outlet for tampering, offering insights into types of opioids tampered with, specific methods and tools used for tampering, how well formulations can be tampered with, and uptake of tampering solutions by the body [41, 42, 44, 49, 50]. It will come as no surprise to researchers frequenting drug discussion forums that published data are cited amongst users as evidence of which drugs (or way of using drugs) gives the desired effects.…”
Section: Methodsmentioning
confidence: 99%